Exploring chemical diversity in Glycine max cultivars: A multivariate approach in the search for bioactive compounds against Spodoptera cosmioides - Aguiar, Maria Clara Santana; Mueller de Freitas, Marcelo; de Freitas, Carlos Alessandro; Boiça Júnior, Arlindo Leal; Carneiro, Renato Lajarim; da Silva, Maria Fátima das Graças Fernandes; Fernandes, João Batista; Forim, Moacir Rossi (Frontiers in Plant Science, 2022)
Soybean crop is regulated by abiotic and biotic stresses with great potential in reducing grain yield and quality. The selection of resistant cultivars is a promising approach for mitigating these damages. We evaluated the chemical profile of Glycine max leaves from different cultivars in order to explore their defense mechanisms against Spodoptera cosmioides caterpillars. We optimized solid-liquid extraction techniques using ultrasound bath and static headspace extraction. Additionally, we developed an approach based on liquid and gas chromatography for analyzing the chemical profile of G. max cultivars. The principal component analysis allowed the classification of transgenic cultivars, which are classified as susceptible to S. cosmioides, from those obtained by genetic improvement and resistant to the insect. Differences were observed in the abundance of phenolic glycosides, lipids, aldehydes, and alcohols. More specifically, S. cosmioides resistant cultivars presented molecules related to the jasmonic and salicylic acid pathways. Such data can contribute to a molecular understanding of phenotypic diversity in soybean cultivars, from plant quality to resistance mechanisms and adaptation, to environmental stress and herbivory.